Evaluasi Faktor-Faktor Penyebab Longsor dan Kesesuaian Mitigasi: Evaluation of Factors Causing Landslides and Suitability of Mitigation - Fathoni, Bulkin; Saputra, Erlangga; Gofar, Nurly (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2024)
Management and maintenance of slopes require proper knowledge of slope conditions so that appropriate mitigation measures can be implemented. The activities required for the management of slopes include slope inventory, slope inspection, slope risk level assessment, and risk mitigation measures. The objective of this study was to observe the slope conditions and causes of past slope failures, determine the appropriate mitigation measures, and analyze the suitability of landslide mitigation measures and causes of slope failures. The research locations are road segment No. 36 (Kota Lahat – Simpang Air Dingin), No. 37 (Simpang Air Dingin – Pagar Alam), and No. 38 (Pagar Alam – Tanjung Sakti – batas Bengkulu). The research was initiated by analyzing data collected by the South Sumatra National Road Management Agency (BPJNSS) from 2018 to 2021. The field observation was conducted on ten locations where the slope had been repaired after slope failure events. The suitability of mitigation with the factors that cause landslides was analyzed using the slope management system method suggested by the Ministry of PUPR. The results showed that most slope failures were triggered by high-intensity rain falling on slope surfaces containing high humidity due to previous rainfall. The common types of slope mitigation are reducing the forces that cause movement, increasing the resisting forces by controlling seepage, and the use of anchors.